Big Data : A Road Map for Successful Digital Marketing - Abadia, Rhodora; Aggarwal, Kriti; Ahmad, Ashfaq; Balamurugan, S.; Bansal, Rohit; Baral, Manish Mohan; Cervantes Flores, Oliver Moisés; Cervantes, Valeria Meléndez; Cervera, Claudia Malcón; Chimhundu, Ranga; De la Vega Meneses, José Gerardo; Dhaya, R.; et al. (De Gruyter, 2022)
Imagine being able to target an audience made up of highly qualified and purchase-ready prospects and easily building them into loyal clients by anticipating their needs and hence offering true value. This is the power of big data for digital marketing. Big Data: A Roadmap for Successful Digital Marketing explores recent trends in the use of big data to predict consumer behavior, strategies to engage online customers, integration of big data with other data sources, and its applications in social media analytics, mobile marketing, search engine optimization and customer relationship management. As the marketing world moves into a data-focused future, the success of marketing efforts will be wholly based on attention to detail in data analysis and effectively acting on insights in order to implement changes that will deliver improved results. This book will help professionals succeed in their digital marketing efforts as well as provide food for thought for students and researchers in the fields of digital marketing, customer behavior and big data analytics.